Electronic Marketing and its Impact on Institutional Entrepreneurship: A Field Study in Yemeni Private Universities in the Capital Municipality of Sana’a - Musallam, Bassam Ali Ahmed; Ghawth, Ghaleb Abdullah Ghaleb (University of Science and Technology Journal for Management and Human Sciences, 2025)
The study aimed to determine the impact of electronic marketing on institutional entrepreneurship in Yemeni private universities in the Capital Municipality of Sana’a. The analytical descriptive approach was used in the study. The study population consisted of all senior and middle management directors and electronic marketing specialists in Yemeni private universities in the Capital Municipality of Sana’a. The study population consisted of all senior and middle management directors and electronic marketing specialists in (9) Yemeni private universities in the Capital Municipality of Sana’a that have been established for more than ten years and whose strategic visions included an entrepreneurial dimension. Due to the small size of the study population, a comprehensive census method was used, and (220) questionnaires were distributed to the members of the population. The findings revealed that there is a positive impact of electronic marketing dimensions (electronic product, electronic promotion, and electronic distribution) except for electronic pricing on institutional entrepreneurship in Yemeni private universities under study. The electronic product dimension had the most significant impact on institutional entrepreneurship, while the electronic distribution dimension had the least impact. The study recommends that universities should strive to achieve advanced levels of entrepreneurship and continuously work on improving the dimensions of electronic marketing. This can be achieved by aligning the design of electronic educational products with the needs of their customers, enabling them to seize new opportunities in the labor market, and achieving a level of integration among the dimensions of electronic marketing, with a focus on the electronic product as the most influential element in the institutional entrepreneurship of universities.